Monitoring Aspergillus flavus genotypes in a multi-genotype aflatoxin biocontrol product with quantitative pyrosequencing - Shenge, K.C.; Adhikari, B.N.; Akande, A.; Callicott, K.A.; Atehnkeng, J.; Ortega Beltran, A.; Kumar, P. Lava; Bandyopadhyay, Ranajit; Cotty, P.J. (Frontiers Media, 2019)
Aflatoxins pose significant food security and public health risks, decrease productivity and profitability of animal industries, and hamper trade. To minimize aflatoxin contamination in several crops, a biocontrol technology based on atoxigenic strains of Aspergillus flavus is commercially used in the United States and some African countries. Significant efforts are underway to popularize the use of biocontrol in Africa by various means including incentives. The purpose of this study was to develop quantitative pyrosequencing assays for rapid, simultaneous quantification of proportions of four A. flavus biocontrol genotypes within complex populations of A. flavus associated with maize crops in Nigeria to facilitate payment of farmer incentives for Aflasafe (a biocontrol product) use. Protocols were developed to confirm use of Aflasafe by small scale farmers in Nigeria. Nested PCR amplifications followed by sequence by synthesis pyrosequencing assays were required to quantify frequencies of the active ingredients and, in so doing, confirm successful use of biocontrol by participating farmers. The entire verification process could be completed in 3–4 days proving a savings over other monitoring methods in both time and costs and providing data in a time frame that could work with the commercial agriculture scheme. Quantitative pyrosequencing assays represent a reliable tool for rapid detection, quantification, and monitoring of multiple A. flavus genotypes within complex fungal communities, satisfying the requirements of the regulatory community and crop end-users that wish to determine which purchased crops were treated with the biocontrol product. Techniques developed in the current study can be modified for monitoring other crop-associated fungi.